Worth Their Salt Too More Notable But Often Unnoted Women of Utah - Whitley, Colleen (University Press of Colorado, 2000)
A follow-up to the highly successful Worth Their Salt, published in 1996, Worth Their Salt, Too brings together a new set of biographies of women whose roles in Utah's history have not been fully recognized, despite their significance to the social and cultural matrix, past and present, of the state. These women-community and government leaders, activists, artists, writers, scholars, politicians, and others-made important contributions to the state's history and culture. Some of them had experiences that reveal new aspects of the state's history, while others simply led lives so interesting that their stories beg to be told. This new collection demonstrates, as Worth Their Salt did, the diversity of Utah's society and the many different roles women have played in it.